2023
DOI: 10.3390/su15065129
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Social Networking Sites and Determining Its Impact on Brand Image and Online Shopping: An Empirical Study

Abstract: Social networking influencers are those who use images, videos, and other updates on social media platforms to affect consumers’ impressions of a company or product. The purpose of this study is to assess the present status of social networking sites and the online purchase intentions of consumers. This research paper is an attempt to identify the effect of various attributes of social networking that influence credibility and brand image, eventually leading to the purchase intention of consumers in Delhi NCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 93 publications
0
10
0
1
Order By: Relevance
“…The discriminant validity indicates how much the measure is adequately distinguishable from related constructs. The Fornell and Larcker criterion is the most popular method for testing discriminant validity [ 63 ] and has been used in many studies of different areas [ 64 , 65 ]. Therefore, this study also adopted the Fornell and Larcker criterion to test the discriminant validity.…”
Section: Resultsmentioning
confidence: 99%
“…The discriminant validity indicates how much the measure is adequately distinguishable from related constructs. The Fornell and Larcker criterion is the most popular method for testing discriminant validity [ 63 ] and has been used in many studies of different areas [ 64 , 65 ]. Therefore, this study also adopted the Fornell and Larcker criterion to test the discriminant validity.…”
Section: Resultsmentioning
confidence: 99%
“…In the enthralling world of China's social media market, entertainment value is critical to the success of micro-influencers (Khan et al, 2023). Micro-influencers must build a compelling experience for their followers, just as a charismatic performer does for his audience (Todorov et al, 2023;Anwar et al, 2021).…”
Section: Micro-influencer Credibilitymentioning
confidence: 99%
“…Vidyanata et al ( 2022) proved that celebrity's credibility have a positive impact on purchase intention with mediation of attitude towards advertisement. Similarly, Khan et al (2023) claimed that attitude towards advertisement plays a vital role as mediator between significant positive relationship between celebrity's credibility and purchase intention. While, Chen et al (2021) found that attitude towards advertisement partially mediates between celebrity's credibility and purchase intention.…”
Section: Celebrity's Congruence Towards Target Audiencementioning
confidence: 99%